The situation of women in the work Kim Ji-young, Born 1982 - Tovar Silva, Yvonne Georgina (2022)
The purpose of this paper is to address the situation of women narrated by the South Korean author Cho Nam-joo in her work Kim Ji-young, born 1982, in order to identify the main labor, family and social problems of women, as well as the pending challenges to ensure the protection and effective enjoyment of their rights in the 21st century. The review of Cho Nam-joo’s work will allow us to understand the importance of the study of law and literature in order to identify different lines of reflection in legal matters and the relevance of promoting research and lines of action in the field of law and gender.